Activation of coagulation system and d-dimer levels in children with acute leukemia - Harun Wijaya; Novie Amelia Chozie; Badriul Hegar (Indonesian Pediatric Society Publishing House, 2014)
Background D-dimer is a molecule as result of breaking down of excessive fibrin formation from the activation of coagulation system. There is evidence of increased activation of coagulation in patients with acute leukemia which was showed by the increment of d-dimer levels. Objective To evaluate the incidence of activation of coagulation sys tem in children with acute leukemia before receiving chemotherapy. Method This cross-sectional study was performed at Dr. Cipto Mangunkusumo Hospital. All newly-diagnosed children with acute leukemia were included in this study, prior to their receiving any chemotherapy treatment. Blast count, prothrombin time (PTI), activated partial thromboplastin time (APTf), and D-dimer levels were examined after the diagnosis was confirmed by morphology and immunophenotyping studies on bone marrow specimens. Results Out of 22 subjects, 13 subjects had increased D-dimer values. The median D-dimer level of this elevated group was 1,000 (range 500-14, 700) n gfmL. In the acute myeloblastic leukemia (AML) patients, activation of coagulation was found in 7 out of 8 subjects. The median D-dimer levels was 950 (range 100-14, 700) ng/mL. In the acute lymphocytic leukemia (ALL) patients, 6 out of 14 subjects had increased activation of coagulation with median D-dimer level of 300 (range 100-3,800) ngfmL. Nine out of 10 subjects with blast cells on peripheral blood smear had a median D-dimer level of 1,000 (range 500-3,800) ng/mL. Both PT and APTT were found normal in all subjects. Conclusion Activation of coagulation sys tem occurs at the time of diagnosis as shown by increased D-dimer levels. The characteristics of activation of coagulation system are different between ALL and AML subjects, as well as between subj ects with positive and negative blast counts on peripheral blood smears. Despite the increased activation of coagulation, PT and APTf remain normal.